Characterization of recombinant human lactoferrin N-glycans expressed in the milk of transgenic cows. - Annabelle Le Parc; Sercan Karav; Camille Rouquié; Elizabeth A Maga; Apichaya Bunyatratchata; Daniela Barile (PLoS ONE)
Lactoferrin (LF) is one of the most abundant bioactive glycoproteins in human milk. Glycans attached through N-glycosidic bonds may contribute to Lactoferrin functional activities. In contrast, LF is present in trace amounts in bovine milk. Efforts to increase LF concentration in bovine milk led to alternative approaches using transgenic cows to express human lactoferrin (hLF). This study investigated and compared N-glycans in recombinant human lactoferrin (rhLF), bovine lactoferrin (bLF) and human lactoferrin by Nano-LC-Chip-Q-TOF Mass Spectrometry. The results revealed a high diversity of N-glycan structures, including fucosylated and sialylated complex glycans that may contribute additional bioactivities. rhLF, bLF and hLF had 23, 27 and 18 N-glycans respectively with 8 N-glycan in common overall. rhLF shared 16 N-glycan with bLF and 9 N-glycan with hLF while bLF shared 10 N-glycan with hLF. Based on the relative abundances of N-glycan types, rhLF and hLF appeared to contain mostly neutral complex/hybrid N-glycans (81% and 52% of the total respectively) whereas bLF was characterized by high mannose glycans (65%). Interestingly, the majority of hLF N-glycans were fucosylated (88%), whereas bLF and rhLF had only 9% and 20% fucosylation, respectively. Overall, this study suggests that rhLF N-glycans share more similarities to bLF than hLF.